Pontine hyperperfusion in sporadic hyperekplexia. Issue 9 (16th August 2007) - Vetrugno, Roberto; Mascalchi, Mario; Vella, Alessandra; Nave, Riccardo Della; Guerrini, Laura; Vattimo, Angelo; del Giudice, Emanuele Miraglia; Plazzi, Giuseppe; D'Angelo, Roberto; Greco, Giovanni; Montagna, Pasquale
Abstract : Objective: To explore with neuroimaging techniques the anatomical and functional correlates of sporadic hyperekplexia. Methods: Two elderly women with sporadic hyperekplexia underwent neurophysiological assessment, MRI of the brain and proton magnetic resonance spectroscopy ( 1 H-MRS) of the brainstem and frontal lobes. Regional cerebral blood flow was investigated with single photon emission tomography (SPECT) during evoked startles and at rest. Results: Both patients showed excessively large and non-habituating startle responses. In both patients, MRI showed impingement of the brainstem by the vertebrobasilar artery, lack of frontal or brainstem abnormalities on 1 H-MRS and hyperperfusion in the dorsal pons and cingulate cortex, and superior frontal gyrus at SPECT during evoked startles. Conclusions: In our patients with hyperekplexia, the vertebrobasilar arteries were found to impinge on the brainstem. Neurophysiological findings and neurofunctional imaging of evoked startles indicated a pontine origin of the movement disorder modulated by activation in cortical, especially frontal, areas. The neurofunctional correlates of evoked startles in human sporadic hyperekplexia are similar to those observed for the startle circuit in animals.